E-commerce environment and trade promotion for Latin America : policy implications from East Asian and advanced economies' experiences - Ueki, Yasushi (ECLAC SantiagoCL, 2003)
Provides information on the recent experiments regarding the introduction of e-commerce and supply chain management. Indicates implications for business and policy makers in Latin America from experiences in East and South-East Asia.